Unraveling DREAM-PL: A Case Report on Challenges and Management - Barrak, Mohammed M.; Al-Aidy, S. R.; Morteza Bonyadi (University of Thi-Qar Journal of Science, 2024)
An uncommon autosomal recessive condition called DREAM-PL syndrome is typified by dysmorphic facial features, renal agenesis, male ambiguous genitalia, microcephaly, polydactyly, and lissencephaly. The CTU2 gene, which is in charge of tRNA post-transcriptional modification, is mutated in the syndrome. This alteration is necessary for the correct translation of genes, and its disruption can result in several aberrant embryonic processes. The severity of DREAM-PL syndrome can vary from moderate to severe, and the clinical characteristics can be diverse. While some patients may exhibit only some of the distinguishing features, others may have all of them. The most common characteristics include ambiguous genitalia, dysmorphic facies, and microcephaly. Diagnosis of DREAM-PL syndrome is typically based on clinical signs and confirmed through genetic testing, which can identify mutations in the CTU2 gene. Material and methodology: In the case being referred to as a study, a 37-week-old male neonate was delivered by lower segment cesarean section. The baby’s birth weight was 2.760 Kg, and a heterozygous CMP mutation of the CTU2 gene was confirmed through whole-exome sequencing (WES). Unfortunately, there is currently no known cure for DREAM-PL syndrome. Result: Treatment focuses on managing the symptoms and providing supportive care. In some cases, surgical correction of birth defects may be beneficial.